Survival of vascularized osseous flaps in mandibular reconstruction: A network meta-analysis - Mubarak Ahmed Mashrah (Public Library of Science (PLoS), 2021)
Objective An evidence regarding which bony flap for reconstruction of mandibular defects following tumour resection is associated with the highest survival rate is still lacking. This network meta-analysis (NMA) aimed to guide surgeons selecting which vascularized osseous flap is associated with the highest survival rate for mandibular reconstruction. Methods From inception to March 2021, PubMed, Embase, Scopus, and Cochrane library were searched to identify the eligible studies. The outcome variable was the flap survival rate. The Bayesian NMA accompanied by a random effect model and 95% credible intervals (CrI) was calculated. Results Twenty-two studies with a total of 1513 patients, comparing four osseous flaps namely fibula free flap (FFF), deep circumferential iliac artery flap (DCIA), scapula flap, and osteocutaneous radial forearm flap (ORFF) were included. The respective survival rates of FFF, DCIA, Scapula, and ORFF were 94.50%, 93.12%, 97%, and 95.95%. The NMA failed to show a statistically significant difference between all comparators (FFF versus DCIA (Odd ratio, 1.8; CrI, 0.58,5.0); FFF versus ORFF (Odd ratio, 0.57; CrI, 0.077; 2.9); FFF versus scapula flap (Odd ratio, 0.25; CrI, 0.026; 1.5); DCIA versus ORFF (Odd ratio, 0.32; CrI, 0.037; 2.1); DCIA versus scapula flap (Odd ratio, 0.14; CrI, 0.015; 1.1) and ORFF versus scapula flap (Odd ratio, 2.3; CrI, 0.16; 34)). Conclusion Within the limitations of the current NMA, FFF, DCIA, Scapula, and ORFF showed a comparable survival rate for mandibular reconstruction. Although the scapula flap reported the highest survival rate compared to other osseous flaps for mandibular reconstruction; however, the decision making when choosing an osseous flap should be based on many factors rather than simply flap survival rate.